2018
DOI: 10.1177/1129729818757977
|View full text |Cite
|
Sign up to set email alerts
|

The Valsalva manoeuvre versus tourniquet for venipuncture

Abstract: This increase in cross-sectional basilic and brachial vein diameters was not different to that obtained with the elastic tube tourniquet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Given these published controversial results, we administered uids only at induction of general anesthesia and mostly in a "mild" form of less than 2 ml/kg body weight. Positive pressure ventilation can also act like a Valsalva maneuver and thus affect vein width [27]. In our study, the respiratory settings were within ranges considered normal, without particularly increased respiratory pressures, and were not altered during measurements for individual patients.…”
Section: Discussionsupporting
confidence: 55%
“…Given these published controversial results, we administered uids only at induction of general anesthesia and mostly in a "mild" form of less than 2 ml/kg body weight. Positive pressure ventilation can also act like a Valsalva maneuver and thus affect vein width [27]. In our study, the respiratory settings were within ranges considered normal, without particularly increased respiratory pressures, and were not altered during measurements for individual patients.…”
Section: Discussionsupporting
confidence: 55%
“…With the development of imaging technologies including ultrasound, the optimized Seldinger PICC placement technique has been derived gradually under ultrasound guidance [ 25 ]. In a large number of clinical studies, the success rate of traditional PICC placement is only 78%, that rises to 84% as modified Seldinger technique was used, and reaches 98% using optimized ultrasound-guided Seldinger PICC placement [ 26 , 27 ]. The ultrasound-guided optimized Seldinger technique has a wide range of great clinical applications for PICC placement.…”
Section: Discussionmentioning
confidence: 99%
“…One must recline the patient into a Trendelenburg position to distend the veins and minimize air embolism -which would unfortunately not be possible in severe dyspnoea or orthopnoea. Using the stethoscope as a tourniquet, [24] forced expiration manoeuvres [25] and occluding the EJV against the clavicle while anchoring the vein using one's thumb and index finger [26] can further augment venous distension. In cases where the patient's mandible is in the way (especially those with short necks or who cannot rotate their necks), one could bend the proximal-third of the angio-catheter slightly to maintain a shallow angle of approach.…”
Section: ) External Jugular Venous Cannulationmentioning
confidence: 99%
“…Villa et al [25] found significant increases in crosssectional basilic and brachial vein diameters following ten seconds of Valsalva manoeuvre compared to tourniquet application, suggesting that a properlyperformed Valsalva could augment venodilation in situations where tourniquet application is not possible (such as EJV cannulation, patients with fragile skin or patients who cannot tolerate tourniquet pain). Lewin et al [45] suggested having patients hum.…”
Section: Forced Expirationmentioning
confidence: 99%